골시멘트 특성 및 스템 형상에 따른 시멘트 타입 인공관절의 생체역학적 평가 - 박흥석; 전흥재; 윤인찬; 이문규; 최귀원 (대한의용생체공학회, 2008)
The total hip replacement (THR) has been used as the most effective way to restore the function of damaged hip joint. However, various factors have caused some side effects after the THR. Unfortunately, the success of the THR have been decided only by the proficiency of surgeons so far. Hence, It is necessary to find the way to minimize the side effect caused by those factors.The purpose of this study was to suggest the definite data, which can be used to design and choose the optimal hip implant. Using finite element analysis (FEA), the biomechanical condition of bone cement was evaluated. Stress patterns were analyzed in three conditions: cement mantle, procimal femur and stem-cement contact surface. Additionally, micro-motion was analyzed in the stem-cement contact surface. The 3-D femur model was reconstructed from 2-D computerized tomography (CT) images. Raw CT images were preprocessed by image processing technique (i.e. edge detection). In this study, automated edge detection system was created by MATLAB coding for effective and rapid image processing. The 3-D femur model was reconstructed based on anatomical parameters. The stem shape was designed using that parameters.The analysis of the finite element models was performed with the variation of parameters. The biomechanical influence of each parameter was analyzed and derived optimal parameters. Moreover, the results of FEA using commercial stem model (Zimmer’s VerSys) were similar to the results of stem model that was used in this study. Through the study, the improved designs and optimal factors for clinical application were suggested. We expect that the results can suggest solutions to minimize various side effects.